Inside the future surviving the technology revolution - Lucas, Henry C. (Praeger, 2008)
"From iPods to E-ZPass technology to YouTube to eGovernment initiatives, the impact of technology is changing our lives more and more each day. This book a counterpart to a Maryland Public Television documentary, chronicles how and why and shows ways people can take advantage of the "revolution" in their personal and professional lives. As technology expert Henry C. Lucas, Jr., argues, the fundamentals of business and the economy - not to mention the details of daily life - are changing in every market, in every industry, and in every nation. His book explores the most significant of these technology-enabled transformations to help readers understand and appreciate the opportunities and threats presented by a new, technology-driven global economy."--Jacket.